A rare presentation of necrotizing sarcoidosis. Issue 6 (10th May 2022) - Sheth, Nirali; Dhamrah, Umaima; Ireifej, Branden; Song, David; Bhuti, Penpa; Singh, Jagbir; Fan, Henry; Ummar, Sibghatallah; Jaiswal, Vikash; Pokhrel, Nishan Babu
Abstract: Sarcoidosis is a disease with unknown aetiology and pathogenesis which affects young adults and is usually a non‐necrotizing granulomatous disease seen in histology. Variants of the disease, such as necrotizing sarcoidosis, were first described by Liebow in 1973 and are rarely seen. This case report describes the case of a 60‐year‐old Bengali female who presented with vague symptoms and was found to have chronic granulomatous inflammation with foci of calcifications involving the lungs, liver and spleen consistent with necrotizing sarcoidosis. Abstract : This case report describes the case of a 60‐year‐old Bengali female who presented with vague symptoms and was found to have chronic granulomatous inflammation with foci of calcifications involving the lungs, liver and spleen consistent with necrotizing sarcoidosis.